Allah dalam Ruang, Waktu, dan Bahasa Manusia: Refleksi Empati Allah Terhadap Manusia - Tri Untoro (EPIGRAPHE: Jurnal Teologi dan Pelayanan Kristiani, 2021)
God is an essence that cannot be limited and understood by humans because God is outside of space and time, and he understanding of human brain. Everything that God does is regardedas a mystery and difficult to understand. How can God be recognized and understood becomes something urgent in human life. By examining and comparing existing literacies, this research present that way God works in time and space. So it can be seen that God is even involved in human space, time and language in His work. God manifests his work as a form of empathy for human suffering. So that humans and the chuch must also imitate the way God works in the world.